2022
DOI: 10.3389/fcvm.2022.1033755
|View full text |Cite
|
Sign up to set email alerts
|

Visualizable vs. standard, non-visualizable steerable sheath for pulmonary vein isolation procedures: Randomized, single-centre trial

Abstract: IntroductionSteerable sheaths (SSs) are frequently used to improve catheter contact during pulmonary vein isolation (PVI) procedures. A new type of visualizable (by electroanatomical mapping system) SS has become available in clinical treatment.PurposeWe aimed to compare procedural data of visualizable vs. non-visualizable steerable sheath assisted PVI procedures in patients with atrial fibrillation (AF).MethodsIn this single-centre randomized study, we enrolled a total of 100 consecutive patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Numerous studies have confirmed the feasibility of near-zero and zero-fluoroscopy approaches for CTI ablation, including their successful application as an extension to pulmonary vein isolation procedures within a single session ( 5 , 15 23 ). In addition, the advent of visualizable steerable sheaths has yielded significant advancements in mitigating radiation exposure during catheter ablation procedures ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the feasibility of near-zero and zero-fluoroscopy approaches for CTI ablation, including their successful application as an extension to pulmonary vein isolation procedures within a single session ( 5 , 15 23 ). In addition, the advent of visualizable steerable sheaths has yielded significant advancements in mitigating radiation exposure during catheter ablation procedures ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the use of ICE, we see the introduction of a visualizable steerable sheath as an additional valuable tool in achieving a zero-fluoroscopy CA approach. According to the recently published data, the use of 3D EAM visualizable steerable sheaths increased the number of procedures that could be performed in a zero-fluoroscopy setting, and reduced left atrial procedure time and RFA time by improving ablation catheter stability, without compromising the efficacy or safety profile of pulmonary vein isolation procedures in the adult population [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steerable sheaths help the operators improve contact and stability of the ablation catheter, leading to achieve efficient lesion formation for AF ablation. Recently, with the advent of visualizable steerable sheaths, RF-PVI is associated with minimal radiation exposure ( 42 , 43 ), and zero-fluoroscopy RF-PVI ( 44 ) showed equal efficacy and safety compared with traditional procedures ( 45 ). Therefore, future direction for AF ablation using cryoballoon and radiofrequency catheter possibly studies better rhythm outcomes, lower complication rates, reduced procedure time, and also reduced radiation exposure.…”
Section: Discussionmentioning
confidence: 99%